Optic nerve sheath ultrasound for the detection and monitoring of raised intracranial pressure in tuberculous meningitis - Donovan, J; Oanh, PKN; Dobbs, N; Phu, NH; Nghia, HDT; Summers, D; Thuong Thuong, NT; Thwaites, GE (Oxford University Press, 2020)
Background: Neurological complications of tuberculous meningitis (TBM) often lead to raised intracranial pressure (ICP) resulting in high morbidity and mortality. Measurement of optic nerve sheath diameter (ONSD) by point-of-care ultrasound may aid in the identification and management of raised ICP in TBM.